2019
DOI: 10.1016/j.ecolind.2018.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Riverine phytoplankton functional groups response to multiple stressors variously depending on hydrological periods

Abstract: Rivers and related freshwater ecosystems are facing increasing natural disturbance and anthropogenic stressors. Understanding the key ecological processes that govern the riverine biota in aquatic ecosystems under multiple pressures has crucial importance. However, there is still insufficient knowledge in quantifying of stressors interactions. Moreover, the understanding of the responses of riverine phytoplankton to multiple stressors is still scarce from catchment aspect. As an interdisciplinary study, the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…Guo et al (2020) calculated short‐period hydrological regime indices (14 and ~28 days before sampling date), and found that these indices override physicochemical variables in structuring riverine diatom traits and community functions. Using structural equation models, Qu et al (2019) observed that the flow regimes (i.e. skewness of 7 days discharge before sampling date) were considered as a key driver for riverine phytoplankton community during two hydrological periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al (2020) calculated short‐period hydrological regime indices (14 and ~28 days before sampling date), and found that these indices override physicochemical variables in structuring riverine diatom traits and community functions. Using structural equation models, Qu et al (2019) observed that the flow regimes (i.e. skewness of 7 days discharge before sampling date) were considered as a key driver for riverine phytoplankton community during two hydrological periods.…”
Section: Discussionmentioning
confidence: 99%
“…This constraint hinders our inference about the major drivers of community structure to one ‘snapshot’ community, which has missed the temporal variation with different mechanisms. For instance, the role of environmental variables on species composition relies upon the extent of their gradients that might change over time (Qu et al, 2019; Wu et al, 2018). Similarly, the biotic interactions and dispersal could also temporally vary that affect species composition.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent studies found that flow regimes over a short-term period (e.g., 7 or 14 days) played a vital role in riverine algae and biofilm communities (Wu et al . 2018; Qu et al . 2019; Guo et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different organisms (e.g., algae, macroinvertebrates, fish, macrophytes, or even terrestrial plants) have distinct extent of response to historical environmental regimes. For instance, recent studies found that flow regimes over a short-term period (e.g., 7 or 14 days) played a vital role in riverine algae and biofilm communities (Wu et al 2018;Qu et al 2019;Guo et al 2020;Guo et al 2021). In contrast, macroinvertebrate and fish communities may show a good response to environmental changes over a longer time period (e.g., 4 weeks, 1 year) (Schneider & Petrin 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Las comunidades de fitoplancton son muy diversas y difíciles de predecir en Kruk, et al (2009); constituyen, además, una fuente importante de alimento y un excelente modelo para interpretar procesos ecológicos como la fotosíntesis, la productividad, el ciclo del oxígeno, el carbono y las relaciones asociadas con la transferencia de energía (Hutchinson, 1967;Harris, 1986;Sommer, 1985;Sommer, 2012;Hilton, et al, 2006;Qu, et al, 2019;Ptacnik, et al, 2008;Rousseaux & Gregg, 2014), que se abordan principalmente a partir de la taxonomía, la diversidad del tamaño y la morfología (Huszar & Caraco, 1998;Bonilla, et al, 2005;Borics, et al, 2007;Rosati, et al, 2017).…”
Section: Introductionunclassified